The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.2147/idr.s408686
|View full text |Cite
|
Sign up to set email alerts
|

Declined Humoral Immunity of Kidney Transplant Recipients to SARS-CoV-2 Vaccines

Abstract: Background Kidney transplant recipients (KTRs) commonly suffer from impaired immunity. KTRs’ compromised immune response to COVID-19 vaccines indicates urgent revision of immunisation policies. Methods A cross-sectional study was conducted in Madinah, Saudi Arabia of 84 KTRs who had received at least one dose of a COVID-19 vaccine. ELISA was used to evaluate anti-spike SARS-CoV-2 IgG and IgM antibody levels in blood samples obtained one month and seven months after vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…( Phattraprayoon et al, 2022 ). Additionally, kidney transplant recipients who were vaccinated with COVID-19 vaccines showed a significant and dramatic decline of antibody levels over time ( Mahallawi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Phattraprayoon et al, 2022 ). Additionally, kidney transplant recipients who were vaccinated with COVID-19 vaccines showed a significant and dramatic decline of antibody levels over time ( Mahallawi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that viral-vector, and heterogenous of all homogenous mRNA-COVID-19 vaccines revealed reduction of levels of anti-S1 IgG between the first and third serum samples [18]. No differences between serum anti-S1 IgG levels at one and six-months after mRNA-COVID-19 vaccination in KTRs with one-month-post-mRNA-COVID-19vaccination-IgG-immune-response seropositivity and different factors through linear regression analysis [18]. Among the immunocompromised population, including KTRs, DPs, PDs, at least three doses of mRNA-COVID-19 vaccination was recommended to be the preparation of choice [20,22].…”
Section: Year Of Publicationmentioning
confidence: 99%